STRUGGLING FOR BALANCE: THE FINANCES OF BAODI COUNTY AROUND WANLI 20. (1st May 2013) - He, Zhaohui
Abstract : The paper studies the local finances of Baodi county, located in north China, around 1592. It provides a case study of county finance immediately after the Single Whip reform in the late Ming. The structure of local finance changed after the reform; however, the fiscal tension between the central government and local governments remained. County magistrates had to face increasing financial pressures constantly. The author demonstrates how, under the strict control of the central government after the Single Whip reform, county magistrates like Yuan Huang managed to maintain financial balance in using fixed revenues to face fluctuating and unexpected expenses.